A True Language of Cinema. Issue 1 (1st March 2023) - Belodubrovskaya, Maria
Abstract: Since cinema communicates meanings through images and sounds, it has long been assumed that it possesses a language—a coded system of units and rules. Cinematic practice is infinitely varied, and it has proven difficult for film theory to pinpoint a language of cinema beyond the assertion that classical continuity codes cinematic illusion. The computational approach presented in James Cutting's Movies on Our Minds: The Evolution of Cinematic Engagement offers a promising new path toward defining a true language of cinema. It shows that mainstream narrative film uses a reliable set of measurable, evolving formal patterns to match the neuropsychological capacities of the average viewer. This article argues that the cinematic "code" Cutting identifies can be elaborated by specifying the minimal narrative unit.